2024
DOI: 10.1038/s41467-023-44475-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequential immunotherapy and targeted therapy for metastatic BRAF V600 mutated melanoma: 4-year survival and biomarkers evaluation from the phase II SECOMBIT trial

Paolo A. Ascierto,
Milena Casula,
Jenny Bulgarelli
et al.

Abstract: No prospective data were available prior to 2021 to inform selection between combination BRAF and MEK inhibition versus dual blockade of programmed cell death protein-1 (PD-1) and cytotoxic T lymphocyte antigen-4 (CTLA-4) as first-line treatment options for BRAFV600-mutant melanoma. SECOMBIT (NCT02631447) was a randomized, three-arm, noncomparative phase II trial in which patients were randomized to one of two sequences with immunotherapy or targeted therapy first, with a third arm in which an 8-week induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Updated 4-year OS data from SECOMBIT trial continue to show superior survival benefit with first-line combination immunotherapy with or without an initial induction course of targeted therapy. 32…”
Section: Targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Updated 4-year OS data from SECOMBIT trial continue to show superior survival benefit with first-line combination immunotherapy with or without an initial induction course of targeted therapy. 32…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…However, the “sandwich approach,” which includes an initial induction course of targeted therapy followed by immunotherapy maintenance, could be used in patients with rapidly progressing disease and was shown to be of clinical benefit in the SECOMBIT trial. Updated 4-year OS data from SECOMBIT trial continue to show superior survival benefit with first-line combination immunotherapy with or without an initial induction course of targeted therapy 32 …”
Section: Systemic Therapies In Melanoma Brain Metastasesmentioning
confidence: 99%
“…The best-known examples include sun-induced melanomas with high tumor mutation burden and BRAF V600E mutations, smoking-related lung carcinomas with KRAS G12C substitutions, and microsatelliteunstable colorectal tumors with kinase-activating genetic alterations, which are potentially sensitive both to immune therapy and to inhibitors of the MAPK pathway [37,98,156]. For example, clinical studies on BRAF V600E mutant melanomas revealed that the overall survival is higher in patients who received BRAFi/MEKi after disease progression during immune therapy when compared to subjects treated with BRAFi/MEKi upfront and ICIs as a second-line [157,158]. Furthermore, combined administration of BRAFi/MEKi and ICIs seems feasible in patients who developed resistance to these drugs previously given as sequential treatment [159].…”
Section: Ccnd1-3 Gene Amplificationmentioning
confidence: 99%
“…The combination of immune checkpoint inhibitors targeting cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) and programmed death 1 (PD-1) has demonstrated heightened efficacy in advanced melanoma, albeit with notable side effects. Comparative studies of ipilimumab plus nivolumab, nivolumab alone, and ipilimumab alone reveal superior outcomes for the combination and nivolumab alone, emphasizing improved response rates, progression-free survival, and overall survival [ 85 , 86 , 87 , 88 , 89 ]. Sequential immunotherapy followed by targeted therapy proves to be beneficial in untreated BRAFV600-mutant metastatic melanoma, highlighting the potential for tailored treatment sequences.…”
Section: Clinical Trials Of Combinationmentioning
confidence: 99%